Adhesion of individually formed fiber post adhesively luted with flowable short fiber composite - Suni Anton O.; Lassila Lippo V.J.; Tuokko Jarno K.; Garoushi Sufyan; Vallittu Pekka K. (United Kingdom, 2025)
This laboratory study aimed to measure the push-out bond strength of individually formed fiber-reinforced composite (FRC) post luted with flowable short fiber-reinforced composite (SFRC) and to evaluate the influence of post coating with light-cured adhesive. Post spaces (Ø 1.7 mm) were drilled into 20 single-rooted decoronated premolar teeth. Post spaces were etched and treated with light-cured universal adhesive (G-Premio Bond). Individually formed FRC posts (Ø 1.5 mm, everStick) were luted either with light-cured SFRC (everX Flow) or conventional particulate-filled (PFC) dual-cure luting cement (G-CEM LinkForce). Half of the posts from each group were treated with dimethacrylate adhesive resin (Stick Resin) for 5 min before luting. After storage in water for two days, the roots were sectioned into 2 mm thick disks (n = 10/per group). Then, a push-out test-setup was used in a universal testing machine to measure the bond strength between post and dentin. The interface between post and SFRC was inspected using optical and scanning electron microscopy (SEM). Data were statistically analyzed using analysis of variance ANOVA (p = .05). Higher bond strength values (p < .05) were obtained when flowable SFRC was used as a post luting material. Resin coating of a post showed no significant effect (p > .05) on bond strength values. Light microscope images showed the ability of discontinuous short fibers in SFRC to penetrate into FRC posts. The use of flowable SFRC as luting material with individually formed FRC posts proved to be a promising method to improve the interface adhesion.